2008
DOI: 10.1128/iai.01019-07
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Type IV Pili to the Virulence of Aeromonas salmonicida subsp. salmonicida in Atlantic Salmon ( Salmo salar L.)

Abstract: Aeromonas salmonicida subsp. salmonicida, a bacterial pathogen of Atlantic salmon, has no visible pili, yet its genome contains genes for three type IV pilus systems. One system, Tap, is similar to the Pseudomonas aeruginosa Pil system, and a second, Flp, resembles the Actinobacillus actinomycetemcomitans Flp pilus, while the third has homology to the mannose-sensitive hemagglutinin pilus of Vibrio cholerae. The latter system is likely nonfunctional since eight genes, including the gene encoding the main pilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 40 publications
1
61
0
1
Order By: Relevance
“…This type of pili is important in a number of bacterial processes, such as flagellumindependent 'twitching' motility, DNA uptake, adherence to surfaces, and biofilm formation (Graupner et al, 2000;Mattick, 2002;Tomich et al, 2007;Boyd et al, 2008). It has been speculated before that in M. mobilis, this pilus may serve as a specific phage receptor (Kalyuzhnaya et al, 2008).…”
Section: Mobility and Adhesion Functionsmentioning
confidence: 99%
“…This type of pili is important in a number of bacterial processes, such as flagellumindependent 'twitching' motility, DNA uptake, adherence to surfaces, and biofilm formation (Graupner et al, 2000;Mattick, 2002;Tomich et al, 2007;Boyd et al, 2008). It has been speculated before that in M. mobilis, this pilus may serve as a specific phage receptor (Kalyuzhnaya et al, 2008).…”
Section: Mobility and Adhesion Functionsmentioning
confidence: 99%
“…In addition, several genes responsible for colonization were found in the P1 genome. The syp genes, a group of genes described in V. fischeri that promote symbiotic colonization and biofilm formation via Sigma54 regulation (Yip et al, 2005), and the flp genes for biogenesis of type IV Flp pilus described in Actinobacillus actinomycetemcomitans (Boyd et al, 2008), may represent important loci for the process of coral colonization. In addition, strain-specific genes found in the P1 genomes revealed the importance of phage genes driving intra-species diversification.…”
Section: Vibrio Coralliilyticus Genome E De O Santos Et Almentioning
confidence: 99%
“…A tapA mutant constructed by allelic exchange was found to be slightly less pathogenic than wild type when delivered by intraperitoneal injection (Masada et al, 2002). Boyd et al (2008) showed that the Tap pilus also made a moderate contribution to virulence in Atlantic salmon (Salmo salar), while the Flp pilus made little or no contribution. In addition to type IV pili, A. salmonicida has also a type I or Fim pilus system (similar to Pap fimbriae of Escherichia coli) encoded by several genes clustered into an operon.…”
Section: Adhesinsmentioning
confidence: 99%
“…salmonicida contains in its genome a complete set of genes for two type IV pilus systems, Tap and Flp (Boyd et al, 2008). In vivo experiments in rainbow trout (Oncorhynchus mykiss) showed that the Tap pilus contributes moderately to virulence.…”
Section: Adhesinsmentioning
confidence: 99%